APLIKASI MOBILE DETEKSI PENYAKIT DEMODEKOSIS PADA ANJING MENGGUNAKAN METODE CONVOLUTIONAL NEURAL NETWORK - Ardy Wijaya; Duman Care Khrisne; Lie Jasa (Program Studi Teknik Elektro UNUD, 2021)
Demodex is a skin disease in dogs caused by the protozoan mite Demodexfollicularumvar canis or Demodex canis. These mites are found in the hair roots and sometimesin the glands, almost the entire life cycle of this type of mite is on the skin, if it lasts for a longtime it can cause death in dogs that are infested by these lice This study aims to detectdemodicosis in dogs with a mobile application using a convolutional neural network methodwith a squeezenet architecture model with radam optimization. This application works by takingpictures directly through the cellphone camera then processing it with a trained model then theoutput of this application displays the probability value of the dog being indicated as demodexor not. Based on the results of testing using the black box testing method, the overallfunctionality of the application has been declared successful in accordance with its respectivefunctions and objectives. From the results of validation data testing using 60 validation data,based on the accuracy demodecosis detection application is able to recognize validation datacorrectly as many as 45 data and 15 data has not been properly recognized, so that theaccuracy value is 75% and the f1-score value is 0,595.